The Function of Renalase - (:unkn) unknown (My University, 2016)
Renalase was originally reported to be an enzyme secreted into the blood by the kidney to lower blood pressure and slow heart rate. Despite multiple reports claiming to confirm this activity in vivo there has been considerable discord in regards to the reaction catalyzed by renalase. The structural topology of renalase resembles that of known flavoprotein oxidases, monooxygenases and demethylases, but the conserved active site residues are unique to renalase. It has been reported that the catalytic function of renalase is to oxidize circulating catecholamines, however in vitro studies have failed to demonstrate a catalytic activity in the presence of such molecules. We have identified renalase as a novel oxidase enzyme which catalyzes the oxidation of both 6-dihydro NAD(P) and 2-dihydro NAD(P) to β-NAD(P)+ delivering the electrons harvested to dioxygen forming hydrogen peroxide. Catalysis involves the oxidation of the dihydropyridyl ring of the substrate by transferring two electrons to the flavin cofactor, followed by release of the oxidized β-NAD(P)+ product, and then the reoxidation of the reduced cofactor. Renalase substrates, 2-dihydro and 6-dihydro NAD(P) are thought to arise from non-specific reduction of NAD(P)+ or tautomerization of NAD(P)H. These aberrant nicotinamide isomers are potent inhibitors of dehydrogenase enzymes including those of glycolysis and the TCA cycle. It would therefore appear that the function of renalase is to eliminate this inhibitory threat to primary metabolism. In addition to identifying the true catalytic substrates and proposing a metabolic function we have also identified verifiably active forms of renalase from Psuedomonas phaseolicola and Pseudomonas aeruginosa, as well as crystal structures of renalase from P. phaseolicola in complex with β-NAD+ and β-NADH. The data presented in this dissertaion chronolog the discovery of a genuine catalytic role for renalase that is likely an important housekeeping function for all life forms.
Keywords: Analytical Chemistry; Biochemistry; Biology; Chemistry; Microbiology; Molecular Biology